Dyadic Flexibility in Early Parent–Child Interactions: Relations with Maternal Depressive Symptoms and Child Negativity and Behaviour Problems. Issue 3 (20th November 2012) - Lunkenheimer, Erika S.; Albrecht, Erin C.; Kemp, Christine J.
<x xml:space="preserve">Abstract</x> Lower levels of parent–child affective flexibility indicate risk for children's problem outcomes. This short‐term longitudinal study examined whether maternal depressive symptoms were related to lower levels of dyadic affective flexibility and positive affective content in mother–child problem‐solving interactions at age 3.5 years (N = 100) and whether these maternal and dyadic factors predicted child emotional negativity and behaviour problems at a 4‐month follow‐up. Dyadic flexibility and positive affect were measured using dynamic systems‐based modelling of second‐by‐second affective patterns during a mother–child problem‐solving task. Results showed that higher levels of maternal depressive symptoms were related to lower levels of dyadic affective flexibility, which predicted children's higher levels of negativity and behaviour problems as rated by teachers. Mothers' ratings of child negativity and behaviour problems were predicted by their own depressive symptoms and individual child factors, but not by dyadic flexibility. There were no effects of dyadic positive affect. Findings highlight the importance of studying patterns in real‐time dyadic parent–child interactions as potential mechanisms of risk in developmental psychopathology. Copyright © 2012 John Wiley & Sons, Ltd.